2018
DOI: 10.3390/rs10060872
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Urban Land Cover of a Large Area Using Multiple Sensors Multiple Features

Abstract: Concerning the strengths and limitations of multispectral and airborne LiDAR data, the fusion of such datasets can compensate for the weakness of each other. This work have investigated the integration of multispectral and airborne LiDAR data for the land cover mapping of large urban area. Different LiDAR-derived features are involoved, including height, intensity, and multiple-return features. However, there is limited knowledge relating to the integration of multispectral and LiDAR data including three featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…Not only does its high spatial resolution allows for detailed image segmentation (Figure 4), the various structural, spectral and textural features derived from LiDAR data were also found to be the most important classification features overall. This is in line with a study by Chen, Du, Wu, et al [39], which concluded that height-related LiDAR features were more important compared to spectral features for urban land cover mapping. Whereas basic land cover classes could be readily differentiated using only LiDAR data, the added value of spectral data, and particularly of hyperspectral data, increased significantly when considering thematically more detailed urban (green) classes (Table 3).…”
Section: Mapping Functional Urban Green Types Using Remote Sensing Datasupporting
confidence: 92%
See 1 more Smart Citation
“…Not only does its high spatial resolution allows for detailed image segmentation (Figure 4), the various structural, spectral and textural features derived from LiDAR data were also found to be the most important classification features overall. This is in line with a study by Chen, Du, Wu, et al [39], which concluded that height-related LiDAR features were more important compared to spectral features for urban land cover mapping. Whereas basic land cover classes could be readily differentiated using only LiDAR data, the added value of spectral data, and particularly of hyperspectral data, increased significantly when considering thematically more detailed urban (green) classes (Table 3).…”
Section: Mapping Functional Urban Green Types Using Remote Sensing Datasupporting
confidence: 92%
“…Over time, many approaches have been suggested to allow for more detailed urban mapping. Firstly, fusion of spectral data with LiDAR (Light Detection and Ranging) data has been successfully applied in urban areas for land cover mapping [38][39][40][41][42], tree species classification [43], urban green mapping [44], detection of invasive shrub species [45] and tree health estimation [46] due to the high complementarity between spectral data and spatially very detailed structural information derived from 3D LiDAR data. Secondly, hierarchical (or stratified) classification approaches (i.e., classification done at multiple thematic levels, where each level is used as a constraint to map the next, more detailed level) have been shown to increase the mapping accuracy of detailed land cover classes [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative assessments of the four SMWF methods are shown in Table 2. The results were evaluated based on overall accuracy (OA), Kappa coefficient (KC), average producer's accuracy (APA), and average user's accuracy (AUA) [41,42]. Only mixed pixels in the flooding fraction images were included when calculating the evaluation indices.…”
Section: Results and Analysismentioning
confidence: 99%
“…High-resolution remotely sensed imagery provides detailed spatial and structural information and thus offers new avenues for precise land cover classification over urban areas [3,4]. However, high spatial resolution does not indicate high precision for computer interpretation.…”
Section: Introductionmentioning
confidence: 99%